Optimization of pyrazole-containing 1, 2, 4-triazolo-[3, 4-b]thiadiazines, a new class of STAT3 pathway inhibitors. Issue 15 (1st August 2016) - LaPorte, Matthew G.; Wang, Zhuzhu; Colombo, Raffaele; Garzan, Atefeh; Peshkov, Vsevolod A.; Liang, Mary; Johnston, Paul A.; Schurdak, Mark E.; Sen, Malabika; Camarco, Daniel P.; Hua, Yun; Pollock, Netanya I.; et al.
Graphical abstract: Abstract: Structure–activity relationship studies of a 1, 2, 4-triazolo-[3, 4- b ]thiadiazine scaffold, identified in an HTS campaign for selective STAT3 pathway inhibitors, determined that a pyrazole group and specific aryl substitution on the thiadiazine were necessary for activity. Improvements in potency and metabolic stability were accomplished by the introduction of an α-methyl group on the thiadiazine. Optimized compounds exhibited anti-proliferative activity, reduction of phosphorylated STAT3 levels and effects on STAT3 target genes. These compounds represent a starting point for further drug discovery efforts targeting the STAT3 pathway.